Neuromuscular blockade monitoring in pediatric patients - Ozgen, Zehra Serpil Ustalar (Anesthesia and pain medicine (Korean society of anesthesiologists), 2024)
The administration of neuromuscular blocking agents (NMBAs), the cornerstone of pediatric anesthesia, facilitates intubation and muscle relaxation during surgery. However, NMBAs can also lead to serious complications including respiratory depression, residual paralysis, and prolonged recovery. Neuromuscular monitoring (NMM) in pediatric patients is therefore essential, as it is in adults, to ensure adequate paralysis during surgery and prompt recovery from NMBA-induced paralysis. This article aimed to provide a comprehensive overview of NMM in pediatric anesthesia including the various available methods, their advantages and disadvantages, and the importance of a standardized NMM approach.